2012
DOI: 10.1089/jmf.2010.1224
|View full text |Cite
|
Sign up to set email alerts
|

Doenjang, a Fermented Soybean Paste, Decreased Visceral Fat Accumulation and Adipocyte Size in Rats Fed with High Fat Diet More Effectively Than Nonfermented Soybeans

Abstract: Soybean is known to have an anti-obesity effect. We compared the anti-obesity effect of doenjang, a fermented soybean paste, with that of nonfermented soybeans in rats. Steamed soybeans and doenjang (steamed soybeans fermented and aged for 10 months) were sampled and freeze-dried. Male Sprague-Dawley rats were fed basal (BA) (5% fat), high fat (HF) (30% fat), HF+steamed soybeans (SOY), or HF+doenjang (DJ) diet ad libitum for 8 weeks. HF significantly increased body weight gain, liver weight, hepatic triglyceri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 34 publications
4
54
0
2
Order By: Relevance
“…No difference in these parameters was detected between the M-HF, BSM-HF, and HF groups. Our data are consistent with the findings of a previous study showing that steamed soybeans and doenjang (steamed soybeans fermented and aged for 10 months) suppressed body weight gain and elevation of hepatic triglyceride and cholesterol levels in Sprague-Dawley rats fed a high-fat (30%) diet for 8 weeks [46].…”
Section: Am Effects On the Levels Of Serum Total Cholesterol And Fecasupporting
confidence: 93%
“…No difference in these parameters was detected between the M-HF, BSM-HF, and HF groups. Our data are consistent with the findings of a previous study showing that steamed soybeans and doenjang (steamed soybeans fermented and aged for 10 months) suppressed body weight gain and elevation of hepatic triglyceride and cholesterol levels in Sprague-Dawley rats fed a high-fat (30%) diet for 8 weeks [46].…”
Section: Am Effects On the Levels Of Serum Total Cholesterol And Fecasupporting
confidence: 93%
“…34 Recently, antiobesity effects of doenjang have been observed in animals, 35,36 which may have been due to constituents such as genistein activating the transcription of carnitine palmitoyltransferase-I, a rate regulating enzyme for fatty acid oxidation, and peroxisome proliferator-activated receptor-alpha target genes involved in fatty acid beta oxidation. 25,34,35 However, doenjang is a unique soybean paste fermented by diverse microorganisms, which uses Bacillus subtilis and B. licheniformis and molds such as Rhizopus, Mucor, and Aspergillus oryzae from rice straw and local environments instead of inoculation. 37,38 Recently, 16S rRNA cloning and sequencing, PCR-DGGE, and 454 pyrosequencing were used to analyze the bacterial community of finally fermented doenjang and revealed that its dominant microbes are Staphylococcus equorum, Enterococcus faecium, Tetragenococcus halophilus, Leuconostoc mesenteroides, and Staphylococcus gallinarum.…”
Section: Discussionmentioning
confidence: 99%
“…20 Recently, doenjang research has focused on its excellent nutritional value as well as its health-promoting properties, such as its antioxidant, 21 fibrinolytic, 22 antimutagenic, 23 anticancer, 24 and antiobesity effects. 25 However, its effect on gut microbiota, particularly endotoxins, has not been studied.…”
Section: Introduction Hmentioning
confidence: 99%
“…Study shows that when viscous dietary fiber is ingested, the expression of CPT-1B in the muscle increased significantly along with improvement in the level of stored fat [11]. Also, in another report, it was found that the stored fat level and TG concentration level decreased at the same time while the expression of CPT-1 increased following an 8 week of high-fat diet combined with fermented soybean paste [18]. These study results are similar to the results with FABP in our study.…”
Section: Discussionmentioning
confidence: 86%